The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7754/clin.lab.2016.151230
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carbohydrate-Deficient Transferrin in Pancreatic Diseases of Different Etiologies

Abstract: Acute and chronic alcoholic pancreatitis, but not biliary pancreatitis, may affect CDT levels. Pancreatitis does not invalidate the use of CDT as a marker of alcohol abuse. CDT can be a useful test for distinguishing alcoholic from non-alcoholic pancreatitis. Changes in CDT level indicate disturbances in transferrin glycosylation in the course of alcoholic pancreatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, transferrin is a negative acute-phase protein, whose concentration decreases during inflammatory responses [ 4 ]. Previously, we reported the changed profile of carbohydrate-deficient transferrin (a sum of the asialo, monosialo and disialo isoforms of transferrin, CDT for short) in pancreatic diseases, including pancreatitis of different etiologies (alcoholic and biliary) [ 5 ] and in pancreatic cancers [ 6 ]. It has been also shown that transferrin sialylation can be a potential prognostic marker for the severity of acute pancreatitis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, transferrin is a negative acute-phase protein, whose concentration decreases during inflammatory responses [ 4 ]. Previously, we reported the changed profile of carbohydrate-deficient transferrin (a sum of the asialo, monosialo and disialo isoforms of transferrin, CDT for short) in pancreatic diseases, including pancreatitis of different etiologies (alcoholic and biliary) [ 5 ] and in pancreatic cancers [ 6 ]. It has been also shown that transferrin sialylation can be a potential prognostic marker for the severity of acute pancreatitis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%